Enhancement of physical and reaction to fire properties of crude glycerol polyurethane foams filled with expanded graphite. (August 2018) - Gama, Nuno V.; Silva, Rui; Mohseni, Farzin; Davarpanah, Amin; Amaral, V.S.; Ferreira, A.; Barros-Timmons, Ana
Abstract: The reation to fire of polyurethane foams (PUFs) has been a subject of increasing relevance, so in this study the reaction to fire performance of PUFs derived from crude glycerol (CG) has been improved using expanded graphite (EG). The influence of different loadings of EG on the physical–mechanical properties of composite foams has been assessed and the results obtained show that it has significant positive impact. Moreover, the reaction to fire of the PUF and EG/PUF composites has been investigated and the results obtained showed that the fire behavior of composite foams containing as little as 5 wt% of EG are significantly improved. Indeed a dramatic reduction of the rate of heat release, mass loss rate, effective heat of combustion and specific extinction area, has been observed even for a relative low amount of EG. Likewise, the use of Infrared Thermography as a function of time has proven that, when EG is used, the combustion stops suddenly and the temperature drops sharply compared with the behavior of the unfilled PUF sample, which suggests that EG acts like a flame extinguisher. The results obtained have proven the suitability of CG for the production of PUFs and that the addition of EG considerably improves the reaction to fire of composite foams. Highlights: Crude glycerol was successfully used to produce ecofriendly PUFs. The fire response of EG/PUFs composites was evaluated. Addition of EG to crude glycerol PUFs enhanced the mechanical properties of the ensuing composites. The fire response of composite PUFs using as little as 5 wt% of EG was significantly improved. IR thermography revealed that EG acts like a flame extinguisher as in its presence combustion stops suddenly.